Enhanced Photocurrent of the Ag Interfaced Topological Insulator Bi2Se3 under UV- and Visible-Light Radiations - Chih-Chiang Wang; Pao-Tai Lin; Fuh-Sheng Shieu; Han-Chang Shih (Nanomaterials, 2021)
Bi2Se3 is a topological quantum material that is used in photodetectors, owing to its narrow bandgap, conductive surface, and insulating bulk. In this work, Ag@Bi2Se3 nanoplatelets were synthesized on Al2O3(100) substrates in a two-step process of thermal evaporation and magnetron sputtering. X-ray diffractometer (XRD), high-resolution transmission electron microscopy (HRTEM), Raman spectroscopy, and x-ray photoelectron spectroscopy (XPS) revealed that all samples had the typical rhombohedral Bi2Se3. Field-emission scanning electron microscopy (FESEM)-energy dispersive x-ray spectroscopy (EDS), XPS, and HRTEM confirmed the presence of the precipitated Ag. The optical absorptance of Bi2Se3 nanoplatelets in UV-visible range decreased with the Ag contents. Results of photocurrent measurements under zero-bias conditions revealed that the deposited Ag affected photosensitivity. A total of 7.1 at.% Ag was associated with approximately 4.25 and 4.57 times higher photocurrents under UV and visible light, respectively, than 0 at.% Ag. The photocurrent in Bi2Se3 at 7.1 at.% Ag under visible light was 1.72-folds of that under UV light. This enhanced photocurrent is attributable to the narrow bandgap (~0.35 eV) of Bi2Se3 nanoplatelets, the Schottky field at the interface between Ag and Bi2Se3, the surface plasmon resonance that is caused by Ag, and the highly conductive surface that is formed from Ag and Bi2Se3. This work suggests that the appropriate Ag deposition enhances the photocurrent in, and increases the photosensitivity of, Bi2Se3 nanoplatelets under UV and visible light.